2015
DOI: 10.2196/jmir.4989
|View full text |Cite
|
Sign up to set email alerts
|

General Practitioners’ Concerns About Online Patient Feedback: Findings From a Descriptive Exploratory Qualitative Study in England

Abstract: BackgroundThe growth in the volume of online patient feedback, including online patient ratings and comments, suggests that patients are embracing the opportunity to review online their experience of receiving health care. Very little is known about health care professionals’ attitudes toward online patient feedback and whether health care professionals are comfortable with the public nature of the feedback.ObjectiveThe aim of the overall study was to explore and describe general practitioners’ attitudes towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 60 publications
6
69
0
Order By: Relevance
“…We identified five key themes in these comments: anonymity of comments, inability to respond without breaching confidentiality, representativeness, moderation of feedback and type of platform. In line with previous work in both the UK and elsewhere, [12][13][14] our analysis supports the hypothesis that doctors feel wary of online patient feedback, perceive its content to be largely negative, question whether it represents the patient population and thus whether it should drive service changes. Recent work indicates that doctors' views on the representativeness of online feedback may be justifiable.…”
Section: Discussionsupporting
confidence: 89%
“…We identified five key themes in these comments: anonymity of comments, inability to respond without breaching confidentiality, representativeness, moderation of feedback and type of platform. In line with previous work in both the UK and elsewhere, [12][13][14] our analysis supports the hypothesis that doctors feel wary of online patient feedback, perceive its content to be largely negative, question whether it represents the patient population and thus whether it should drive service changes. Recent work indicates that doctors' views on the representativeness of online feedback may be justifiable.…”
Section: Discussionsupporting
confidence: 89%
“…[8][9][10][11][12][13] Increasingly, the internet is being harnessed alongside the plethora of more traditional tools, such as paper based questionnaires, to gather patient experience data. 14 Online methods of collating patient feedback have distinctive features when compared to traditional forms, including the breaking of geographical barriers, providing the opportunity for honest, real-time and transparent dialogue, and possibly encouraging more patients to provide their feedback. 11 Despite few healthcare professionals asking patients to report their feedback online, some patients are doing so and many are reading online feedback from others.…”
Section: Introductionmentioning
confidence: 99%
“…This study builds on the existing literature on physician authority and the doctor-patient relationship by considering the effects of reviews on physician authority through mediating components of reputation and expertise. Research has shown both physicians' general wariness of reviews (Patel et al, 2015;Mueller et al, 2013) and the reflexive, thoughtful potential of reviews (Adams, 2011). This article analyzes reviews and surgeons' reactions to them together, showing how even surgeons who receive positive reviews fear their potential threat to their reputations.…”
Section: Medical Consumerism and Cosmetic Surgerymentioning
confidence: 99%